Penanaman Bibit Pohon Buah sebagai Upaya Konservasi Tanah dan Peningkatan Ekonomi Warga di Kota Malino - Herman Sjahruddin; Irfai Sohilauw; A. Sulfati; Muh.Umar Data; Siti Mispa; Khaeril Khaeril; Heslina Heslina; Elyas Albar (Lembaga Pengembangan Kinerja Dosen, 2026)
Malino City in Gowa Regency plays a crucial ecological role as a water catchment area, yet it currently faces the threat of land degradation due to land-use conversion and erosion in hilly areas. This community service activity aims to implement soil conservation while enhancing the economic potential of local residents through the planting of productive fruit tree seedlings. The methods employed include educational socialization, training on planting techniques for sloped land, and the distribution of superior fruit tree seedlings (avocado, durian, and orange). The results indicate an increase in community understanding regarding the importance of permanent vegetation in maintaining soil stability. A total of [Mention number] tree seedlings were planted with the active participation of local farmer groups. In conclusion, the integration of ecological and economic aspects through productive trees creates a sustainable conservation system by providing direct financial benefits to the community, thereby increasing their motivation to preserve the environment in the Malino region.